Evaluation of the water quality of a high Andean lake using different quantitative approaches - Valdiviezo Gonzales, Lorgio Gilberto (2023)
This study assessed a high Andean lake’s trophic state and water quality using methodologies with eutrophication and water quality indexes. Water samples were collected at six points in the lake, with a monthly frequency, for three winter and three summer months. Dissolved oxygen, pH, phosphates, nitrates, transparency, chlorophyll-a, fecal coliforms, biological oxygen demand (BOD), temperature, and turbidity were determined at each point. The trophic state of the lake was categorized by applying the Organization for Economic Cooperation and Development (OECD) eutrophication index, Carlson’s trophic state index (CTSI) and trophic index (TRIX). In addition, National Sanitation Foundation water quality index (NSF-WQI), Canadian Water Quality Index (CCME-WQI) and Oregon Water Quality Index (OWQI) were used to evaluate water quality. Results indicated that the lake had a high level of eutrophication, suggesting an excessive accumulation of nutrients in the water. CTSI and TRIX index showed that the lake was in a hyper-eutrophic state, while according to the OECD methodology, the trophic state related to phosphorus and transparency was hypereutrophic, and according to chlorophyll, it varied from mesotrophic to eutrophic. The NSF index classified the lake with average quality, the CCME index indicated fair water quality, and the OWQI classified it as very poor. Therefore, the water quality of the high andean lake assessed by eutrophication and water quality indexes presented significant differences based on physicochemical characteristics. The human influence was identified as the main cause of eutrophication, including tourism and agriculture. These results suggest that measures should be taken to reduce human activity in the area and control pollution in the lake.